(untitled) (Jurnal Ipteks Terapan, 2024)
Introduction: Pain is a traumatic experience for children. 78% of children experience painful consequence puncture needle at least very every cycle take care stay. Wrong One source of pain in children is venipuncture. Objective: To identify the effectiveness of passive distractive measures used to reduce pain in children undergoing venipuncture procedures. Method: The structure of this research is a detailed analysis using the PRISMA diagram procedure. Researchers applied the PICO method and searched for articles in English published between 2013 and 2023. Several databases used included ProQuest, PubMed, ScienceDirect, and Scopus. Researchers used the Confidence tool for data selection and extraction processes, and utilized the JBI instrument to assess the articles retrieved. Results: Ten articles were identified and analyzed. All articles have RCT design studies. The sample sizes of the reported studies ranged from 56 to 216 conducted in Türkiye and Italy. From a literature search, it was found that Passive distraction technique used to reduce pain levels in children undergoing venipuncture that is watch cartoon animation listen music, as well as kaleidoscope. Conclusion: Passive distraction techniques can reduce pain in children due to venous surgery puncture. Technique distraction passive Can form watch cartoon, listen music, and kaleidoscope.